2015
DOI: 10.1097/shk.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte Damage

Abstract: Cardiac arrest is considered to be a cause of small bowel ischemia, but the consequences of cardiac arrest on the human small bowel have been rarely studied. Plasma citrulline concentration is a marker of functional enterocyte mass, and plasma intestinal fatty acid-binding protein (I-FABP) concentration is a marker of enterocyte damage. We aimed to measure enterocyte biomarkers after cardiac arrest and to study the prognostic value of biomarker abnormalities. This is a prospective, observational, single-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
2
22
0
2
Order By: Relevance
“…These results should be interpreted with caution, since there was a high pre-test probability. Nevertheless, citrulline remains a potential accurate marker for AMI, since it has been shown to be a reliable marker of functional enterocyte mass [ 24 ], prognostic value of mortality in the ICU [ 60 ], and NOMI after cardiac arrest [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results should be interpreted with caution, since there was a high pre-test probability. Nevertheless, citrulline remains a potential accurate marker for AMI, since it has been shown to be a reliable marker of functional enterocyte mass [ 24 ], prognostic value of mortality in the ICU [ 60 ], and NOMI after cardiac arrest [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some human and prospective studies have suggested that gut injury could also contribute to the vasoplegia observed in the post-resuscitation shock through its ability to provoke or worsen a systemic inflammatory response [ 27 29 ]. Indeed, in post-CA patients, markers of intestinal injury are increased and endotoxemia is frequent [ 27 , 28 ], this latter being associated with the severity of vasoplegia [ 29 ]. However, its incidence is still unknown and the relationship between post-resuscitation shock and gut injury is complex, as the two are closely intertwined.…”
Section: Pathophysiology Of Post-resuscitation Shockmentioning
confidence: 99%
“…30,31 A few studies indicated presence of low serum citrulline concentrations in critically ill patients. [32][33][34] Plasma citrulline concentrations <20 µmol/L were noted in 50%-68% of patients at ICU admission. [33][34][35] A plasma citrulline concentration of <20 µmol/L has been shown to be indicative of a decrease in enterocyte mass.…”
Section: Hamada Et Al Reported That Ultrasonographic Measurement Of G...mentioning
confidence: 99%